An overview of physical and chemical properties method for fruits and/or vegetables / Iqbal Hakim Halim, Mohd Haris Ridzuan Ooi Abdullah and Ch'ng Pei Eng - Halim, Iqbal Hakim; Abdullah, Mohd Haris Ridzuan Ooi; Ch'ng, Pei Eng (2020)
The paper reviews recent studies on the method of obtaining physical and chemical properties of fruits and/or vegetables which pointing out the characteristics of the fruits. Some of the authors describe the fruits as underutilized fruits because the species is unexposed to the public with its advantages and currently being handled manually. Additionally, the journal mostly highlighted the purposes of the fruits and/or vegetables to humans. This study aims to determine the best method of acquiring physical and chemical properties of fruits and/or vegetables to provide applicable details in order to contribute an improvement to practical information to ease machine design for handling and processing.